Use of single-item scales in the evaluation of German digital health applications (DiGAs): Scoping review protocol - Julian Wienert; Mahin Mohammadi (PLOS One, 2026)
Introduction German Digital Health Applications (DiGAs) are reimbursable, patient-facing digital interventions within the German healthcare system that must demonstrate positive healthcare effects. Outcome measurement in DiGA evaluations is influenced by both methodological considerations and feasibility requirements in real-world care settings. In practice, these evaluations may be affected by factors such as limited patient adherence, high dropout rates, and variability in real-world data quality, which can complicate outcome data collection. Single-item scales may offer a low-burden alternative to multi-item instruments; however, their use, justification, and limitations in DiGA evaluations have not been comprehensively mapped. This paper presents a scoping review protocol designed to address this gap. Methods and analysis This protocol outlines a scoping review that will follow the Joanna Briggs Institute methodology and be reported in accordance with PRISMA-ScR guidelines. The review will apply the PCC framework, focusing on DiGAs listed in the BfArM DiGA directory, the use of single-item scales, and evaluations conducted within the German healthcare system. Studies will be identified primarily through the DiGA directory and supplemented by PubMed searches to verify and complete bibliographic information. Two reviewers will independently screen and verify extracted data. Quantitative data will be summarized descriptively, while qualitative information on constructs, rationales, and methodological considerations will be analyzed thematically. Results As this is a protocol, no results are reported. The planned review will provide a descriptive overview of single-item scale use in DiGA evaluations, map the constructs assessed, and identify methodological characteristics and gaps. Conclusion This protocol outlines a transparent and reproducible approach to mapping outcome measurement practices in DiGAs. The findings of the completed review will inform researchers, developers, and policymakers and support methodological development in regulated digital health contexts. Registration The scoping review protocol is registered at the Open Science Framework under the following DOI https://doi.org/10.17605/OSF.IO/A3PM5 .